2016
DOI: 10.1186/s12859-016-1271-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of large disjoint motifs in biological networks

Abstract: BackgroundBiological networks provide great potential to understand how cells function. Network motifs, frequent topological patterns, are key structures through which biological networks operate. Finding motifs in biological networks remains to be computationally challenging task as the size of the motif and the underlying network grow. Often, different copies of a given motif topology in a network share nodes or edges. Counting such overlapping copies introduces significant problems in motif identification.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…This is a well studied problem in the literature. We use the method developed by Elhesha et al [12] for this step as it is one of the most recent and efficient methods. One can however replace this step with another method for F 1 count without affecting the rest of our algorithm.…”
Section: Counting Partial Overlapping Motifsmentioning
confidence: 99%
“…This is a well studied problem in the literature. We use the method developed by Elhesha et al [12] for this step as it is one of the most recent and efficient methods. One can however replace this step with another method for F 1 count without affecting the rest of our algorithm.…”
Section: Counting Partial Overlapping Motifsmentioning
confidence: 99%
“…CoMoFinder is developed based on a parallel subgraph enumeration strategy to efficiently and accurately identify composite motifs in large TF-miRNA co-regulatory networks. Rasha Elhesha and Tamer Kahveci [27] in 2016, proposed a motif centric algorithm for finding motifs in a target network. The core idea of this method is to build a set of basic building patterns and find instances of these patterns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The analysis was limited to motifs of ≤ 4 nodes. First, because it has been shown that the fundamental regulatory 555 sub-network patterns consist of a small number of nodes networks (Baiser et al, 2015;Elhesha and Kahveci, 2016;Milo et al, 2002;Yeger-Lotem et al, 2004). Second, because the number of possible motif topologies grow exponentially with number of nodes making it impossible to test larger motif sizes.…”
mentioning
confidence: 99%
“…We also created multiple 560 shuffled networks that have the same number of nodes and edges with the RT network and set a z-score as 2.54 for a sub-graph to be considered as a motif present in the network. Is important to note that the motif frequency (i.e., the number of times a given motif appears in a given network) do not monotonically decrease or increase with the motif size and the statistical significance of the motif abundance is independent of the motif size and topology (Elhesha and Kahveci, 2016). This 565 is because motif count does not have downward closure property and a motif is considered as abundant in a given network only if its frequency is significantly higher than the number of times the same motif appears in randomized networks (p-value <0.01).…”
mentioning
confidence: 99%
See 1 more Smart Citation